Hubungan Vulva Hygiene, Budaya Dan Asupan Protein Dengan Penyembuhan Luka Perineum Pada Masa Nifas Di BPM Bidan Dwi Ngarti Dan BPM Bidan Ernawati Kota Depok Tahun 2022: (Relationship between Vulva Hygiene, Culture, and Protein Intake with Perineal Wound Healing in the Postpartum Period at BPM Midwife Dwi Ngarti and BPM Midwife Ernawati Depok City in 2022 - Sulastri, Fitri (Dohara POAJ, 2023)
Introduction: The majority of the labor that occurs is a normal type of labor through the vagina. The removal of the baby's entire body through the vagina during the normal delivery process causes the tearing of the birth canal. Perineal tearing occurs in almost all the first childbirth and not infrequently also in subsequent labor. The incidence of perineal rupture in Indonesia in 2017 was experienced by 75% of women who gave birth vaginally, it was found that out of a total of 1,951 women who gave birth spontaneously vaginally, 57% of women received perineal stitches, namely 28% due to episiotomy and 29% due to spontaneous tears The purpose of this study is to determine the relationship between personal hygiene, culture, and protein with the healing of perineal wounds during the puerperium at BPM Midwife Dwi Ngarti and at BPM Midwife Ernawati Depok City in 2022. Methods: This research is a quantitative type that is analytical in nature with a cross-sectional approach. In this study, the population was pregnant women at BPM Midwife Dwi Ngarti Depok as many as 30 people and the sample used Total Sampling. Researchers used the Chi-Square test. Results: Based on the results of the study Frequency distribution is known that the majority of rapid healing of wounds during puerperium at BPM Midwife Dwi Ngarti and at BPM Midwife Ernawati Depok City amounted to the number of wounds with rapid healing was 28 people (56,0%) and the number of events that recovered quickly during the puerperium period was 22 people (44,0%). Discussion: The conclusion of this study is that there is a relationship between the variable’s vulva hygiene, culture, and protein intake with perineal wound healing during the puerperium at BPM Midwife Dwi Ngarti and BPM Midwife Ernawati Depok City in 2022.